2015
DOI: 10.1007/s11127-014-0221-z
|View full text |Cite
|
Sign up to set email alerts
|

How do elections affect international cooperation? Evidence from environmental treaty participation

Abstract: Is there a strategically beneficial time for political leaders to make international environmental commitments? Based on the political cycles theory, we argue that leaders have incentives to delay costly ratification of international environmental agreements to the post-electoral period. However, the cost of participating in these agreements is often lower for developing countries, and they may enjoy indirect advantages, which may make them more prone to ratifying in the pre-electoral period. These hypotheses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Second, cycles are likely to be stronger at local level since institutions are less developed and media scrutiny weaker than at the national level (Khemani, ; Eslava, , for instance). Third, political leaders may not only rely on fiscal tools to maximize their reelection prospects, but use various possible tools (Dubois, ), such as the levels of regulated prices (Paiva, ; Özatay, ; Sukhtankar, ), recruitment of state employees (Levitt, ; Labonne, ; Cahan, ), development assistance (Faye and Niehaus, ), or international cooperation (Cazals and Sauquet, ). Exploring further these avenues would enrich the understanding of political cycles and political strategies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, cycles are likely to be stronger at local level since institutions are less developed and media scrutiny weaker than at the national level (Khemani, ; Eslava, , for instance). Third, political leaders may not only rely on fiscal tools to maximize their reelection prospects, but use various possible tools (Dubois, ), such as the levels of regulated prices (Paiva, ; Özatay, ; Sukhtankar, ), recruitment of state employees (Levitt, ; Labonne, ; Cahan, ), development assistance (Faye and Niehaus, ), or international cooperation (Cazals and Sauquet, ). Exploring further these avenues would enrich the understanding of political cycles and political strategies.…”
Section: Resultsmentioning
confidence: 99%
“…Despite significant heterogeneity, many studies find that incumbents “try to make the year before an election a ‘happy one’ in order to be reelected” consistent with Paldam's expectations (Paldam, , p. 324). Cazals and Sauquet () and Dubois () argue that cycles are more likely to occur for instruments, including fiscal policy, rather than for outcomes of economic policy, such as employment, growth, or inflation. They suggest that this may explain why the literature has been increasingly focused on political budget cycles (PBCs, hereafter) rather than on political business cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies show that policy decisions are influenced by the partisan composition and the ideological orientation of parties in government (e.g., Bräuninger, ; Cazals & Sauquet, ; Cusack, ; Hibbs, ; Imbeau, Pétry, & Lamari, ; Martin & Vanberg, ; Schmidt, ; Schulze, ; Tosun, ). The basic argument is that political parties represent specific segments in the electorate, which have specific interests.…”
Section: State Of Research and Theoretical Argumentmentioning
confidence: 99%
“…To reduce this gap, we are interested in learning how the ideological composition of cabinets and the presence of parties with a specific ideological background and particular interests that hold ministerial posts affect the regulation of GMOs. Several studies revealed that ideological orientations and policy‐specific positions of political parties have an impact on legislative outputs (see, e.g., Bräuninger, ; Cazals & Sauquet, ; Cusack, ; Hibbs, ; Martin & Vanberg, ; Schmidt, ; Schulze, ). But how does the partisan composition of a government, its programmatic orientation, and the allocation of cabinet offices in (coalition) governments affect policy making in a specific issue like biotechnology?…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we separate from the electoral process for the tractability of the model and focus on their potential effects on political parties. Based on empirical evidence, Cazals and Sauquet (2015) show that political leaders' levels of commitment to IEAs differ based on the timing of elections. Buchholz et al (2005) provide a theoretical examination of the implications of the electoral process for IEAs, and find significant adverse effects.…”
Section: Introductionmentioning
confidence: 99%